2019
DOI: 10.3390/rs11040460
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MERRA-2 Surface PM2.5 over the Yangtze River Basin: Ground-based Verification, Spatiotemporal Distribution and Meteorological Dependence

Abstract: A good understanding of how meteorological conditions exacerbate or mitigate air pollution is critical for developing robust emission reduction policies. Thus, based on a multiple linear regression (MLR) model in this study, the quantified impacts of six meteorological variables on PM2.5 (i.e., particle matter with diameter of 2.5 µm or less) and its major components were estimated over the Yangtze River Basin (YRB). The 38-year (1980–2017) daily PM2.5 and meteorological data were derived from the newly-releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 47 publications
(109 reference statements)
3
47
0
Order By: Relevance
“…Moreover, the model underestimated aerosol loadings over central India. Other studies have reported biased low AOD and corresponding PM2.5 concentrations over other polluted regions (He et al, 2019;Song et al, 2018). Nov. 24 th , on the other hand, represented a day with no significant fire emission.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, the model underestimated aerosol loadings over central India. Other studies have reported biased low AOD and corresponding PM2.5 concentrations over other polluted regions (He et al, 2019;Song et al, 2018). Nov. 24 th , on the other hand, represented a day with no significant fire emission.…”
mentioning
confidence: 86%
“…The MERRA-2 PM2.5 was based on the mass mixing ratios of black carbon, organic carbon, dust, sea-salt, and sulfate. Since ammonium concentration is not available, it is common in the literature to assume that sulfate ion will 210 be completely neutralized by ammonium and form ammonium sulfate and therefore a factor of 1.375 was assumed in calculating inorganic aerosol concentrations (Buchard et al, 2016;He et al, 2019;Provençal et al, 2017). On the other hand, literature suggest organic carbon concentration should be multiplied by 1.4 to compensate for other missing organic compounds to estimate the organic mass (Buchard et al, 2016;Chow et al, 2015;He et al, 2019;Provençal et al, 2017;Turpin and Lim, 2001).…”
Section: Observation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Open Access that the PM2.5 time series estimated from the MERRA-2 aerosol reanalysis in the same way as described in He et al (2019) was used. The one more correlated to this external PM2.5 time series was then used as the reference (deemed as homogeneous) while the other was considered as the base series (i.e., implies to be adjusted).…”
Section: Construction Of Reference Seriesmentioning
confidence: 99%
“…Air quality is influenced by a variety of meteorological and socioeconomic factors [4,5,6,7,8,9,10]. However, a number of empirical studies, primarily in developed countries, demonstrated that urban form, such as size, shape, population density, compactness, and fragmentation has an important effect on local air pollution [11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%